Service-oriented Leadership of Educational Institution Administrators under the Nakhon Ratchasima Primary Educational Service Area Office 1 - Mungfaoklang, Chamrat; Kohtbantau, Sunthon; Asasing, Suwat; Sawandee, Somdet; Boonthom, Cheewin (Interdisciplinary Academic and Research Journal, 2023)
Background and Aims: Educational institution administrators must change their perspective and attitude and learn to be open-minded and not cling to previous ideas or knowledge. This is considered a great change in innovative leadership. Innovative leadership will result in being able to perform duties to obtain innovations or new things that are beneficial to educational institutions and can develop education with quality. Thus, the purposes of this research were 1) to study the strategic leadership of school administrators. under the Office of Nakhon Ratchasima Primary Educational Service Area 1. 2) to compare the strategic leadership of school administrators. Under the Office of Nakhon Ratchasima Primary Educational Service Area, Region 1, classified by position and the size of the educational institution. Methodology: The sample used in this research was 311 school administrators and teachers. The research tool was a 5-point estimation scale questionnaire. The consistency index was obtained between 0.80-1.00 and the reliability of the entire questionnaire was 0.86. Statistics used for data analysis included frequency, percentage, mean, and standard deviation. t-test and F-test. Results: The research results found that; (1) Strategic leadership of educational institution administrators Nakhon Ratchasima Primary Educational Service Area Office, Region 1, as a whole, was at a high level. (2) Educational institution administrators and teachers with different positions Have opinions on the strategic leadership of educational institution administrators Under the jurisdiction of the Nakhon Ratchasima Primary Educational Service Area Office, Area 1, classified by position. Overall, they are significantly different at the .05 level, except for the ability to use various input factors to formulate strategies. and having expectations and creating opportunities for the future are no difference. (3) School administrators and teachers working in educational institutions of different sizes have opinions on the strategic leadership of school administrators Under the Office of Nakhon Ratchasima Primary Educational Service Area 1, the overall picture was significantly different at the .05 level. Conclusion: The educational administrators’ strategic leadership in Nakhon Ratchasima Education Area Office, District 1, is at a high level. Differences in opinions on strategic leadership exist among administrators and teachers based on positions and school sizes, with statistical significance except for certain aspects like formulating strategies and future expectations.